Year season on epicuticular waxes in leaves of Echinodorus grandiflorus (Cham. & Schltdl.) Micheli (Alismataceae) - Joaquim, Walderez Moreira; Ono, Elizabeth Orika [UNESP]; Salatino, Maria Luiza Faria; Rodrigues, João Domingos [UNESP] (My University, 2010)
The paper aimed to study the influence of different seasons of the year on epicuticular waxes in Echinodorus grandiflorus plants and to analyze the profile of nalkanes in epicuticular waxes. The experiment used adventitious plantlets from the flower stem and approximately 10-cm-tall adventitious plantlets with an average of 4 to 5 leaves, planted in 10-liter pots containing a 40% soil, 40% rice hulls, and 20% vermicompost mixture. E. grandiflorus presented an intermediary profile between terrestrial and aquatic plants, with a main homologue C27 (heptacosane), followed by C25 (pentacosane) and C29 (nonacosane). The studies presented here provide information about ecological aspects and chemical and mechanical defenses of Echinodorus grandiflorus.

Este trabalho objetivou estudar a influência das estações do ano sobre o conteúdo de ceras epicuticulares e a análise dos perfis dos n-alcanos da cera em folhas de Echinodorus grandiflorus. No experimento foram utilizadas mudas adventícias com aproximadamente 10 cm de altura e 4 a 5 folhas, que foram plantadas em vasos de 10 L, tendo como substrato a mistura de 40% de terra, 40% de palha de arroz e 20% de húmus de minhoca. Echinodorus grandiflorus apresentou perfil intermediário entre plantas terrestres e aquáticas, apresentando como principal homólogo C27 (heptacosano), seguido de C25 (pentacosano) e C29 (nonacosano). Os estudos realizados fornecem informações sobre os aspectos ecológicos e as defesas químicas e mecânicas de Echinodorus grandiflorus.
Keywords: Phenology; N-alkanes; Aquatic plants; Fenologia; N-alkanos; Planta aquática